Rapid and simple detection of Candida albicans using closed dumbbell-mediated isothermal amplification - Zhang, Yanli; Chen, Xuhan; Zhong, Yeling; Guo, Fei; Ouyang, Guifang; Mao, Rui (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionCandida albicans, a human fungal pathogen, multiplies to invade body cells and causes fungal diseases in the condition of insufficient body's immune function. Early detection of C. albicans is required to guide appropriate prevention and treatment.MethodsThe purpose of this study was to establish a C. albicans assay based on newly developed closed dumbbell-mediated isothermal amplification (CDA) to achieve rapid and simple point of care diagnostic. The CDA technique was carried out by specific primers targeting at the conserved C. albicans ITS2 gene. All primers were selected and evaluated by real-time fluorescence monitoring and endpoint visual judgement indicated by hydroxy naphthol blue (HNB). Optimal primers and accelerate primers (out primers and loop primers) were designed and selected after confirmation of the fundamental CDA primers to achieve more efficient CDA reaction for C. albicans detection (CA-OL-CDA).ResultsAfter establishment of the assay, 9 non-Candida albicans strains, including 3 Candida species were tested to negative by adopting the established CA-OL-CDA assay, indicated high specificity. The limit of detection of Candida albicans DNA by CA-OL-CDA assay was 6.2×10-6 ng/μL of DNA (10 copies/μL), 10-fold more sensitive than real-time quantitative PCR (qPCR).DiscussionThe CA-OL-CDA assay exhibited advantages of high specificity, sensitivity, simpler and more efficient operation. In addition, the CA-OL-CDA method holds potential in on-site detection for C. albicans using color shift by adopting the reaction mixture based on HNB.